2012
DOI: 10.1038/ismej.2012.134
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Vibrionaceae population structure in coastal bacterioplankton

Abstract: How reproducibly microbial populations assemble in the wild remains poorly understood. Here, we assess evidence for ecological specialization and predictability of fine-scale population structure and habitat association in coastal ocean Vibrionaceae across years. We compare Vibrionaceae lifestyles in the bacterioplankton (combinations of free-living, particle, or zooplankton associations) measured using the same sampling scheme in 2006 and 2009 to assess whether the same groups show the same environmental asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 52 publications
8
48
0
Order By: Relevance
“…It is likely that frequent homologous recombination serves as a cohesive force maintaining convergence of species, akin to its role in sexual organisms, and that when local adaptation occurs during invasion of new habitats or niches, if the differential distribution of strains among habitats is strong enough to depress gene flow sufficiently between related genotypes (5,52), certain strains will escape from being homogenized by recombination, and subsequent accumulations of mutations and/or genetic drift within them will eventually lead to independent evolutionary clusters. This trigger-like action of ecological divergence among frequent recombination events in the process of speciation has been observed in some other bacterial populations, especially Vibrionaceae (8,53,54). To some extent, the way S. albidoflavus strains occupy and adapt to a new habitat resembles the widely discussed formation of new ecotypes (6,52), therefore, the observed habitat barriers to recombination in S. albidoflavus clarify the coexistence of homologous recombination and ecological divergence in the diversification of streptomycetes.…”
Section: Discussionmentioning
confidence: 54%
“…It is likely that frequent homologous recombination serves as a cohesive force maintaining convergence of species, akin to its role in sexual organisms, and that when local adaptation occurs during invasion of new habitats or niches, if the differential distribution of strains among habitats is strong enough to depress gene flow sufficiently between related genotypes (5,52), certain strains will escape from being homogenized by recombination, and subsequent accumulations of mutations and/or genetic drift within them will eventually lead to independent evolutionary clusters. This trigger-like action of ecological divergence among frequent recombination events in the process of speciation has been observed in some other bacterial populations, especially Vibrionaceae (8,53,54). To some extent, the way S. albidoflavus strains occupy and adapt to a new habitat resembles the widely discussed formation of new ecotypes (6,52), therefore, the observed habitat barriers to recombination in S. albidoflavus clarify the coexistence of homologous recombination and ecological divergence in the diversification of streptomycetes.…”
Section: Discussionmentioning
confidence: 54%
“…Tamplin et al 1990, Neogi et al 2012. However, in some recent studies both free-living lifestyles or communities associated with aggregates have been reported for Vibrio (Lyons et al 2007, Froelich et al 2013, Szabo et al 2013. A second hypothesis of our study is therefore that Vibrio is found more in particles than free-living in plankton.…”
Section: Introductionmentioning
confidence: 51%
“…As a result, potential niche-specifying genes or alleles are much more readily pinpointed in the Vibrio islands than the Sulfolobus continents. Whether the nascent Vibrio lineages will persist cannot be predicted but we note that 3 yr after the initial sampling, the same populations with the same set of habitat-specific flexible genes were observed once again, suggesting a reasonably stable association between ecological units and selected parts of the genome (Szabó et al 2013). However, we note that, at stage 2, the two nascent populations cannot be differentiated from a single population with the putative nichespecifying genes under balancing or negative frequency-dependent selection within the population Shapiro 2014).…”
Section: Stages In the Speciation Spectrummentioning
confidence: 83%